Impact of Status quo and Resistance to Innovation on the Failure of Detection and Prevention Strategies of Drugs Control Committee in Malaysia - Zeng, Zhen (Frontiers in Psychology, 2022)
The detection and prevention strategies for drug control have gained significant attention from the drug control committees globally and need the researchers’ attention to improve these strategies worldwide. Hence, this research investigates the impact of the status quo (SQ) and resistance to the innovative nature of the drug control committee on the failure of detection and prevention strategies (FDPS) in Malaysia. This article also analyzes the mediating role of poor team performance (PTP) among the SQ and resistance to the innovative nature of the drug control committee and the FDPS in Malaysia. This study has employed the primary data collection ways such as questionnaires to gather the data from selected respondents. The researchers also applied the SPSS-AMOS to check the association among variables and testing of hypotheses. The results revealed that the SQ and resistance to the innovative nature of the drug control committee have a positive association with the FDPS in Malaysia. The findings have also exposed that PTP significantly mediates between the SQ and resistance to the innovative nature of the drug control committee and the FDPS in Malaysia. This study guides the policymakers that they should develop the policies that eliminate the SQ nature and motivate the committee to adopt innovations that enhance the team performance and success of detection and prevention strategies in Malaysia.